Caribbean Report 14-06-1995 - Ransome, Debbie (anchor); Bremner, Juliet (correspondent); Simpson, Myrna (interviewee); Orr, Carol (correspondent); Grant, Bernie (interviewee); Moraes, Claude (interviewee); Richards, Ken (correspondent); Charles, Eugenia (interviewee); Caroit, Jean Michel (correspondent) (The British Broadcasting Corporation, 1995)
In London, the acquittal of the two police officers accused of the manslaughter of Joy Gardner angers relatives and friends of the victim. The Director of the Joint Council for the Welfare of Immigrants, Claude Moraes comments on the involvement of the police in deportations. The West Yorkshire police have ordered an internal inquiry into the events which led Asian youths to riot in the Manningham area of Bradford. An election date for St. Kitts and Nevis is expected to be announced by Prime Minister Kennedy Simmonds. In Dominica, Edison James is sworn in as the island's new Prime Minister. Meanwhile, the ex-Prime Minister, Dame Eugenia Charles, assesses the elections and talks about her plans for retirement. Continuing violent crimes in Western Kingston and South St. Andrews have angered the business community. In the Dominican Republic, 10 persons were injured amid clashes between rioters and police in the the town of Villa Altagarcia. One of the victims is a 13 year-old who was injured by a bullet fired from a jeep owned by the Under-Secretary for Sports. The police chief ordered an investigation of the case. London's Evening Standard newspaper has paid substantial damages to Lady Colin Campbell, the biographer of the Princess of Wales.
1. Headlines with Debbie Ransome (00:00-00:39)
2. Two British police officers have been acquitted of the manslaughter of Joy Gardner (00:40-08:10)
3. Police investigates rioting by Asian youths in the Manningham area of Bradford (08:11-08:43)
4. Prime Minister Kennedy Simmonds is expected to announce the election date for St. Kitts and Nevis (08:44-09:15)
Keywords: Acquittals -- Great Britain; Deportation -- Great Britain; Immigrants -- Government policy -- Great Britain; Blacks -- Great Britain; Riots -- Great Britain; Asians -- Great Britain; Youth -- Social conditions -- Great Britain; Police-community relations -- Great Britain; Conflict of generations; Saint Kitts and Nevis -- Politics and government; Elections -- Saint Kitts and Nevis; Dominica -- Politics and government; Ex-prime ministers -- Dominica; Politicians -- Retirement; Business enterprises -- Jamaica; Violent crimes -- Jamaica; Riots -- Dominican Republic; Violence -- Dominican Republic; Damages; Women biographers -- Great Britain